Work conditions and health of locomotive engineers. I. Noise, vibration, thermal climate, diesel exhaust constituents, ergonomics. - Heino, Marja; Ketola, Ritva; Mkelä, Paavo; Mäkinen, Raine; Niemelä, Raimo; Starck, Jukka; Partanen, Timo (Scandinavian Journal of Work, Environment & Health, 1978)
Noise and vibration were measured in the cabs of 35 locomotives from 15 locomotive series. Noise exposure was estimated from measurements of A-weighted equivalent noise levels with personal noise dose meters. For the evaluation of the frequency .and fluctuation level, noise samples were recorded under different operating conditions. Forty-five percent of the measured equivalent noise levels exceeded 85 dB during a measuring period of 0.52 h. Vibration was measured from the seat of the locomotive cab, at the foot of the seat, and at the floor level. The most harmful vibr·ation was detected between 1 and 3 Hz of the 1/3 octave band, the 8-h risk limit of ISO standard 2631 often being exceeded in this range. The thermal climate in 20 locomotive cabs was evaluated under both summer and winter conditions with the measurement of temperature, velocity, relative humidity of the air, and globe temperature. The results were compared with the international comfort and health standards for climatic conditions. The analyses indicated nonuniform air temperature and draft in the cabs. These discomforts were caused by the cold air flow and the low surface temperature of the windows in winter. The thermal climate parameters often exceeded the comfort limit in summer. Diesel exhaust constituents were measured in the air of four roundhouses and of nine cabs during a trip. Four constituents with the highest dilution coefficients were chosen for measurement, namely, oxides of nitrogen, acrolein, formaldehyde, and total dlL9t. The Finnish threshold limit values of these substances were not exceeded. The highest values were obtained in the sheds, where the exposure times were very short. Ergonomic surveys utilizing spatial measurements, observation, photography, and interviews were made for the ten most common Finnish locomotive series in order to provide for recommendations both for the design of new locomotive types and for the modification of those in use. The features requiring the most urgent attention were connected with climbing in and out of the cab, as well as with the design of the seats, the controls, and the instrument board. The steps were usually in an upright angle, positioned at unequal intervals, and slippery; therefore the ascent and descent were dangerous. The seats were defective in design and poorly adjustable. The seat of the locomotive assistant was unfeasible in many cabs. The arrangement of the dials on the instrument board was often confusing. Many of the controls were far from the engineer and inadequately designed.
Keywords: diesel exhaust constituent; ergonomy; health; locomotive engineer; noise; thermal climate; vibration; work condition